Jasa Titip (JASTIP) Barang Prespektif Hukum Islam dan Hukum Positif : (Studi Kasus Pemilik Akun Instagram @azkaestu) - Satria, Yusca; Abadi, Khafid; Askari, Saif (el hisbah Journal of Islamic Economic Law, 2022)
Goods delivery service (jastip) is a service assistance service to buy certain goods that are presented through web-based media, and for this assistance the perpetrators of the delivery service will receive fees or wages. The owner of the Instagram account @azkaestu provides this web-based buying and selling service by applying the price of goods and estimates combined with the cost or wage rate for the service if the customer does not ask directly, and does not explain what the cost of the store is. Based on the above background, the formulation of the problem in this study are: 1. How is the practice of goods deposit services on the @azkaestu Instagram account owner?, 2. What is the perspective of Islamic law on goods deposit services?, 3. What is the positive legal perspective on goods deposit services? ? The conclusion that can be drawn is the mechanism for determining ujrah on the @azkaestu Instagram account by entering administrative wages which are combined into the product cost price called include. The wage rate for administration usually ranges from 10-50% of the product cost and this depends on the operational services of the goods or the needs of the custodians. Meanwhile, the positive legal view on online application-based transactions involving online deposit services is essentially an engagement.